Macroeconomic And Microeconomic Factors Impact The Health Of Islamic Commercial Banks In Indonesia - Priyo Nugroho, Anton (Al Urwah : Sharia Economics Journal, 2023)
This research aims to analyze the influence of macroeconomic and microeconomic factors on the health level of Islamic commercial banks in Indonesia. The macroeconomic factors used in this study are inflation and interest rates, while the microeconomic factors used are asset growth and third-party fund growth. The health level of banks is measured using the composite value of bank health, assessed through self-assessment by banks using the RGEC method (Risk profile, Good corporate governance, Earnings, Capital). The research data is sourced from the financial reports of 11 Islamic commercial banks in Indonesia for the period 2013-2020. The data analysis technique used is panel data regression. The research results show that inflation, interest rates, and asset growth significantly influence the health level of Islamic commercial banks in Indonesia, while third-party fund growth does not significantly affect the health level in Indonesia.